The Role of Door-to-Door Visits by Bhabinkamtibmas in Preventing Motorcycle Theft at Lembang Police Station - Rusbiyanto, Reynal Dimas Oki Pratama (Advances in Police Science Research Journal, 2024)
The emergence of theft criminal offense especially motor vehicles theft, is caused by the weakness of deterrence and public awareness of crime and orderliness disturbance. Therefore, efforts to maintain the security and order of the community are needed with the implementation of Harkamtibmas by the National Police. In this case, Bhabinkamtibmas has a role to do prevention through the activities of door to door visiting activity. However, in the past few year, there has been an increase in cases of motor vehicle theft in the Lembang Sector Police. Based on the description, several problem formulations were obtained regarding the implementation of the visiting activities, the factors influencing the activities, and the role of the Bhabinkamtibmas in carrying out door-to-door visiting activity. Referring to these conditions, the conceptual literature uses two research results that are relevant to this study. The theory used in this research is based on the role theory, the 6M Management theory (Man, Money, Method, Machine, Market, and Materials), the Management theory (P.O.A.C), the concept of Bhabinkamtibmas, the concept of visiting activities (Door to Door system), and the concept of motor vehicle theft. This research focuses on the role of Bhabinkamtibmas in preventing the crime of motor vehicle theft through Door to Door visiting activity at Lembang Sector Police. Sources used in this research are primary and secondary sources. The data collection techniques used in this study include interviews, observations, and document studies. Thereafter, in data validity, triangulation technique is used in determining the data validation. The data analysis techniques used are data reduction, data feed, and resume. The results obtained are about the implementation of door to door visiting activity where the activity does not yet have a fixed of the Standard Operating Procedure (SOP). In addition, the researcher also found that there were Bhabinkamtibmas officers who were given dual tasks. This cases could happen because there are a few members of the Lembang Sector Police, which makes the door-to-door visiting activity by Bhabinkamtibmas not optimally implemented. The researcher's suggestion is by making a clear Standard Operating Procedure (SOP) which regulating the activities of Bhabinkamtibmas. It aims to make the job desk of the members are in accordance with their responsibilities, so that the Kamtibmas messages can be conveyed optimally to the community.